Analyzing the Merdeka Curriculum Implementation at Pilot Islamic Elementary Schools in Semarang, Indonesia - Purwanti, Kristi Liani; Rofiq, Mohammad; Fashihah, Istin’amatul; Romaniyah, Romaniyah (Journal of Integrated Elementary Education, 2024)
The study is focused on exploring the Merdeka Curriculum implementation at the pilot Islamic elementary schools in Semarang, Indonesia. It specifically examines aspects such as lesson planning, lesson implementation, P5RA implementation, assessment planning, and assessment implementation. The research was conducted using a descriptive qualitative method, gathering data through interviews, field observations, and documentation. The findings revealed that while the schools had incorporated the Merdeka Curriculum teaching module into their lesson planning, there were limitations regarding the variety of learning models and the integration of the Pancasila and Rahmatan Lil Alamin student profiles. Although learning methods varied, monotonous face-to-face teaching remained predominant. Implementing P5RA was effective, mainly through learning-based projects that enhanced student engagement. While the schools utilized various assessment techniques, there was room for improvement in fully integrating 21st-century skills. The assessment process included routine formative and summative assessments but lacked full integration of higher-order thinking skills (HOTS)-based assessment. Based on these findings, the study suggests the need for additional support and training for teachers and adapting learning modules to facilitate student-centered learning better.